GabiPD – The GABI Primary Database integrates plant proteomic data with gene-centric information - Usadel, Björn; Schwacke, Rainer; Nagel, Axel; Kersten, Birgit (Frontiers in Plant Science, 2012)
GabiPD is an integrative plant “omics” database that has been established as part of the German initiative for Genome Analysis of the Plant Biological System (GABI). Data from different “omics” disciplines are integrated and interactively visualized. Proteomics is represented by data and tools aiding studies on the identification of posttranslational modification and function of proteins. Annotated 2DE-gel images are offered to inspect protein sets expressed in different tissues of Arabidopsis thaliana and Brassica napus. From a given protein spot, a link will direct the user to the related GreenCard Gene entry where detailed gene-centric information will support the functional annotation. Beside MapMan- and GO-classification, information on conserved protein domains and on orthologs is integrated in this GreenCard service. Moreover, all other GabiPD data related to the gene, including transcriptomic data, as well as gene-specific links to external resources are provided. Researches interested in plant protein phosphorylation will find information on potential MAP kinase substrates identified in different protein microarray studies integrated in GabiPD’s Phosphoproteomics page. These data can be easily compared to experimentally identified or predicted phosphorylation sites in PhosPhAt via the related Gene GreenCard. This will allow the selection of interesting candidates for further experimental validation of their phosphorylation.